Optimasi Keuntungan Produksi UMKM Keripik Pisang Menggunakan Linear Programming Metode Simpleks Dan Software POM-QM - Salsabilah Daryani; Syaharani Sunggu Aritonang; Suvriadi Panggabean (Lembaga Pengembangan Kinerja Dosen, 2024)
This research focuses on optimizing the profits of UMKM production of banana chips using the simplex linear programming method and the help of POM-QM software. This research aims to find out ways to use profit optimization methods in banana chips MSMEs so that they can find out maximum profits, production costs, income and raw materials used. The method used is a qualitative descriptive method, where the data obtained is more descriptive in nature from the results of interviews and observations that have been carried out and then the data will be analyzed qualitatively. Data collection techniques in this research include the use of primary data and secondary data. Primary data is obtained through observation, interviews, or distribution of questionnaires to relevant sources. Meanwhile, secondary data was obtained through literature searches from books and magazines that were relevant to the research topic. The analysis technique used is linear programming using the simplex method. The research results and discussion show that this function has reached optimal conditions. Therefore, the calculation stops once all the values in the objective function become positive. The result of this solution is the variable value x1 = 6 ; x2 = 2 ; x3 = 0 dan x4 = 0. Increase in profit from the initial value of Rp. 675,000 to reach a maximum profit (Zmaks) of Rp. 900,000, then the difference between profits before and after optimization is IDR. 225,000, and with the help of POM-QM for Windows software calculations become more relevant because this tool helps in completing calculations to achieve maximum profit levels quickly, accurately and efficiently.